Threat under cats' claws: Molecular detection and risk factors for zoonotic Bartonella species in blood and claw samples from cats in Brazil - Cruz, Thais Nascimento de Andrade Oliveira; Gonçalves, Luiz Ricardo [UNESP]; Furquim, Maria Eduarda Chiaradia [UNESP]; André, Marcos Rogério [UNESP]; Munhoz, Alexandre Diaz; Carlos, Renata Santiago Alberto; Silva, Fabiana Lessa (Elsevier, 2022)
Bartonelloses are zoonoses widely dispersed throughout the world caused by bacteria of the genus Bartonella. Domestic cats play an important role in the epidemiology of bartonelloses, since these animals are considered natural hosts of B. henselae, B. koehlerae and B. clarridgeiae. This study aimed to determine the occurrence of Bartonella spp. in domestic cats’ blood and claw samples in the southern region of Bahia, northeastern Brazil. Additionally, the main clinical and hematological changes in Bartonella-positive animals were investigated, as well as the risk factors associated with the infection. For this purpose, 188 indoor house domestic cats were clinically evaluated and submitted to claw and blood sample collection. Additionally, data regarding the clinical history of the animals were recorded. Out of 188 cats’ blood samples, 20.7% (39/188) were positive in the qPCR for Bartonella spp. based on the nuoG gene. Out of 39 claw samples collected, 23.9% (9/39) were positive for Bartonella spp. The parameters of the blood and claw samples ranged from 1.42 to 395,000 and 4.32 - 108,000 copies/μL of a fragment of Bartonella nuoG gene, respectively. The amplified sequences shared identity ranging from 99% to 100% with the three main cat-related Bartonella species. Higher platelet values (p = 0.0082) were observed in animals positive for Bartonella spp. Young and unsterilized cats with outdoor access were more prone to infection by Bartonella spp. The data reported here demonstrated the occurrence of Bartonella spp. in blood and claw samples from cats in northeastern Brazil showing no significant clinical and hematological disorders.
Keywords: Bartonellosis; Cat scratch disease; Feline; qPCR